2011
DOI: 10.3354/meps09168
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive investment in the North Sea haddock: temporal and spatial variation

Abstract: Maturation and fecundity have been examined since the 1970s in 2 putative sub-populations of North Sea haddock Melanogrammus aeglefinus. Reproductive investment within the western North Sea haddock sub-population significantly increased between the 1970s and 2000s, as was evident from both a decline in maturation probability and an increase in fecundity with size. A decline in maturation probability was also evident in males from the east North Sea, although the length at 50% probability of maturing (Lp50) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Earlier studies found shifts towards lower A 50 and L 50 in North Sea cod and haddock stocks from 1983 to 1995 (Rochet 2000b) and in North Sea Norway pout from 1983 to 2006 (Lambert et al 2009). PMRN shifts have also been observed in similar direction for inshore haddock along the Scottish coast between the mid-1970s and the mid-1990s (Wright et al 2011a) and for 3 subpopulations of North Sea cod (Wright et al 2011b). …”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…Earlier studies found shifts towards lower A 50 and L 50 in North Sea cod and haddock stocks from 1983 to 1995 (Rochet 2000b) and in North Sea Norway pout from 1983 to 2006 (Lambert et al 2009). PMRN shifts have also been observed in similar direction for inshore haddock along the Scottish coast between the mid-1970s and the mid-1990s (Wright et al 2011a) and for 3 subpopulations of North Sea cod (Wright et al 2011b). …”
Section: Introductionmentioning
confidence: 65%
“…Wright et al (2011b) found a strong decline in L p50 in the southern and north-western subpopulations of North Sea cod, and a mild decrease in the north-eastern subpopulation, the difference being attributed to stronger selection for early maturing genotypes in the 2 former. Likewise, Wright et al (2011a) showed that the magnitude of changes in maturation probability was greater in western than eastern North Sea haddock.…”
Section: Population Structurementioning
confidence: 99%
See 3 more Smart Citations